THE ROLE OF PHYSICAL EDUCATION IN ADAPTATION STUDENTS - FRESHMEN TO THE CONDITIONS OF STUDY IN THE HIGH SCHOOL (Physical Culture and Sport: Scientific Perspective, 2024)
The article highlights the problem of adaptation of first-year students to the conditions of a higher school. This problem is one of the urgent problems and still remains a traditional subject of discussions among scientists. It is known that the adaptation of student youth to modern life is a complex, multifaceted and long-term process that requires the involvement of various reserves of the young organism, which are not yet fully formed in students who have entered the first year of higher education.Analyzing the developed scientific sources, we studied educational and methodological, scientific and methodological, methodological literature, scientific research works, program documents, systematized this material.Motivation is one of the main sources of activity of elementary school students. It gives the process of physical education a focus on a certain type of activity and significant value. Therefore, the formation of the physical culture of the future specialist is primarily a problem of educating students in a motivational attitude towards it.Analyzing formative and educational practice in institutions of higher education, we see that there is a problem of forming a positive and active attitude of first-year students to the discipline "Physical Education". The negative attitude of students towards attending physical education classes, which has reached the level of general acceptance in Ukraine, has a destructive effect on the general state of their health, on the level of physical development and physical readiness of students for life activities.Scientists see that optimizing the educational process of physical education of students in a higher education institution is one of the ways to improve it. This process is impossible without taking into account the psychophysiological capabilities of students.
Keywords: physical education; adaptation; students; psychological qualities; institutions of higher education; health; prevention; physical activity